The effect of cavity density on the formation of electrostatic shock in the lunar wake: 1-D hybrid simulation - Yuan Jin; Ye Pang (Earth and Planetary Physics, 2020)
One-dimensional hybrid simulations are carried out to study the plasma refilling process in the lunar wake. Previous theoretical and simulation studies have shown that ion-ion acoustic (ⅡA) instability can be initiated and electrostatic shock can be formed under the condition \begin{document}${{T_{\rm e}}\gg {T_{\rm i}}}$\end{document}. We find that the time evolution of ⅡA instability and the formation of electrostatic shock strongly depend on initial cavity density. The initial position of the electrostatic shock is dependent on the ratio between initial cavity density and background solar wind density, i.e., the farther away the initial position, the lower is the ratio. When the initial cavity density is low enough, the density and electric field profile across the wake become much complex. Meanwhile, the back-to-back electrostatic shock is unstable in the case of lower cavity densities; at the late evolution stage, a new shock-like structure can be formed at the central region of the lunar wake.